2015
DOI: 10.1097/mao.0000000000000762
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between Wireless CROS and Bone-anchored Hearing Devices for Single-sided Deafness

Abstract: Comparisons of CROS and BAHD need to be re-evaluated as both technologies have evolved. In our pilot study, both devices seem comparable, with the CROS avoiding the risks of surgery, and we recommend a trial of CROS in our center for first line treatment of single-sided deafness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 30 publications
(59 reference statements)
0
30
0
1
Order By: Relevance
“…Contralateral rerouting of signal (CROS) hearing aids [Bosman et al, 2003;Finbow et al, 2015;Hol et al, 2005;Wazen et al, 2003] and percutaneous bone-anchored hearing devices [Faber et al, 2013;Martin et al, 2010;Stewart et al, 2011;Zeitler et al, 2012] have been proposed for the rehabilitation of SSD with different results. More recently, cochlear implant has been suggested for the rehabilitation of SSD [Arndt et al, 2011;Erbele et al, 2015;van Zon et al, 2015;Vermeire and Van de Heyning, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…Contralateral rerouting of signal (CROS) hearing aids [Bosman et al, 2003;Finbow et al, 2015;Hol et al, 2005;Wazen et al, 2003] and percutaneous bone-anchored hearing devices [Faber et al, 2013;Martin et al, 2010;Stewart et al, 2011;Zeitler et al, 2012] have been proposed for the rehabilitation of SSD with different results. More recently, cochlear implant has been suggested for the rehabilitation of SSD [Arndt et al, 2011;Erbele et al, 2015;van Zon et al, 2015;Vermeire and Van de Heyning, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding mild-to-profound USHL, bone conduction devices, contralateral routing of sound systems, and cochlear implants could be options for auditory rehabilitation. Although previous studies have shown a lack of beneficial effect of bone conduction devices or contralateral routing of sound systems regarding sound localization, speech perception is improved with these devices when speech is presented to the poorer ear [ 25 , 26 ]. Single-sided deafness is now being considered as an indication for cochlear implantation and many studies have reported the benefits of cochlear implantation regarding sound localization, speech perception in noisy environments, and tinnitus [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not only was this effect significant but mean occlusion in dB was comparable to the natural open ear canal, 23 suggesting an absence of occlusion. The combination of these improvements in hearing aid technology over the past several years have led to an increase in adoption and acceptance of CROS 27,28 and BiCROS 29 devices.…”
Section: Contralateral Routing Of Signalmentioning
confidence: 99%
“…[31][32][33][34] Recent studies have found no significant differences in objective or subjective outcomes with new wireless CROS technology compared with osseointegrated bone conduction implants. 27,28,35 The adoption and acceptance of current CROS technology has not only increased but seems to be comparable to that of surgical rerouting solutions. 28 Other benefits of CROS hearing aids include the design and ease of use.…”
Section: Benefits Of Cros Amplificationmentioning
confidence: 99%
See 1 more Smart Citation